Organic Farming in Negros Occidental: Proposed Enrichment - Lamique, Denesa C. (JPAIR Multidisciplinary Research, 2010)
This study determined the extent of implementation of organic farming in some selected areas in the province of Negros Occidental as basis for development of an action plan which would help the farmers in their adoption of the program. In gathering data needed for the study, the researcher-made instrument was used. The instrument was administered to the respondents composed of 10 implementers, 20 organic producers, and 70 organic consumers. The data gathered were statistically treated with the use of mean test to determine the extent of implementation of organic farming. The result of the study revealed that the implementation of organic farming as perceived by the respondents was at moderate extent. Furthermore, this study found out that no significant differences in responses were found to exist on the extent of implementation of organic farming as perceived by the respondents when grouped and compared according to selected variables. It is recommended that the proposed enrichment action plan should be adopted to help farmers on the implementation and their adoption of organic farming.